Control Of Homoclinic Chaos By Weak Periodic Perturbations. - Chacón, Ricardo (World Scientific series on nonlinear science. Monographs and treatises, 2005)
This monograph presents a reasonably rigorous theory of a highly relevant chaos control method: suppressionenhancement of chaos by weak periodic excitations in low-dimensional, dissipative and non-autonomous systems. The theory provides analytical estimates of the ranges of parameters of the chaos-controlling excitation for suppressionenhancement of the initial chaos. The important applications of the theory presented in the book include: (1) control of chaotic escape from a potential well; (2) suppression of chaos in a driven Josephson junction; (3) control of chaotic solitons in FrenkelKo.